DISKRIMINASI PADA PRIA BERGAYA FEMININ - Resi Yulia; Yusuarsono -; Anis Endang SM (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
This study aimed to find out the discrimination in feminine men in Sawah Lebar, Bengkulu. Discrimination occured because people only recognize two sexes, the female and male. In society, gender differences had not only biological implications, but also social and psychological because people have different expectations on the attitude, behavior, and appearance between women and men.This research used a qualitative descriptive approach. Informants were taken by using purposive sampling method. Data were collected by using interview, observation and documentation techniques. The results showed a picture of discrimination as evidenced by marginalization, subordination, stereotyping, violence, and double burden among the feminine men in society. Keywords: discrimination, feminine men, gender differences